Reduced‐dose chemotherapy followed by blinatumomab in induction therapy for newly diagnosed B‐cell acute lymphoblastic leukemia - Jing Lu; Huifen Zhou; Xin Zhou; Yonggong Yang; Laigen Tong; Miao Miao; Xiaofei Yang; Suning Chen (Cancer Medicine, 2024)
Abstract Background Blinatumomab early‐line treatment in B‐cell precursor acute lymphoblastic leukemia (B‐ALL) might improve clinical outcomes. Methods We conducted a retrospective real‐world cohort analysis in 20 newly diagnosed B‐ALL patients who received reduced‐dose chemotherapy (idarubicin, vindesine, and dexamethasone) for 1–3 weeks, followed by blinatumomab for 1–4 weeks as an induction therapy. Results At the end of the induction therapy, a complete remission rate of 100% was achieved; 17 (85%) patients were minimal residual disease (MRD) negative (<1 × 10−4). Adverse events (AEs) were reported in 12 (60%) patients—43.8% were grade 1–2 and 56.2% were grade 3–4. No incidence of neurotoxicity or grade ≥3 cytokine release syndrome was reported. Conclusions Blinatumomab demonstrated a significant improvement in clinical outcomes in patients with newly diagnosed B‐ALL irrespective of their poor‐risk factor status and the pretreatment blast burden.